2022
DOI: 10.3390/jof8080762
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antifungal Activity, Cytotoxicity and QSAR Study of Camphor Derivatives

Abstract: Control of fungal phytopathogens affecting crops and woodlands is an important goal in environmental management and the maintenance of food security. This work describes the synthesis of 37 camphor derivatives, of which 27 were new compounds. Their antifungal effects on six fungi were evaluated in vitro. Compounds 3a, 4a and 5k showed strong antifungal activity against Trametes versicolor, with EC50 values of 0.43, 6.80 and 4.86 mg/L, respectively, which were better than that of tricyclazole (EC50 118.20 mg/L)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Compounds 4k and 4o were evaluated for cytotoxicity against cell lines of LO2 and HEK293 using an MTT assay. As shown in Figure , the results indicated that compounds 4k and 4o had no cytotoxicity against LO2 and HEK293 cell lines at the concentration of 10 μg/mL, and the cell survival rate was close to 100%, which was correlated with our previous findings on camphor derivatives exhibiting low toxicity (nontoxic) for LO2 and HEK293T cells …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds 4k and 4o were evaluated for cytotoxicity against cell lines of LO2 and HEK293 using an MTT assay. As shown in Figure , the results indicated that compounds 4k and 4o had no cytotoxicity against LO2 and HEK293 cell lines at the concentration of 10 μg/mL, and the cell survival rate was close to 100%, which was correlated with our previous findings on camphor derivatives exhibiting low toxicity (nontoxic) for LO2 and HEK293T cells …”
Section: Resultsmentioning
confidence: 99%
“…solani was obtained via inoculation of potato dextrose agar (PDA) plates at 28 °C for 3 days. All reagents were purchased from Shanghai Macklin Biochemical Co., Ltd. (Shanghai, China) and Aladdin Chemical Reagent Co., Ltd. Camphor derivatives were synthesized using the previous methods and confirmed through Fourier transform infrared spectroscopy, hydrogen nuclear magnetic resonance ( 1 H NMR), carbon nuclear magnetic resonance ( 13 C NMR), and high-resolution mass spectrometry …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important renewable natural monoterpene, camphor can be isolated from Cinnamomum camphora, while the synthetic analogue can be produced from turpentine . Camphor has been extensively utilized as a fragrance and food a flavorant in household cleaners as well as a component of hygienic insecticides. Moreover, camphor has been used for the synthesis of many derivatives, which exhibited diverse pharmaceutical activities (Figure b). , Among them, some camphor derivatives were found to exhibit promising antifungal activities against different plant pathogenic fungi. , In addition, camphanic acid was a downstream product of camphor, and its derivatives also displayed promising pharmaceutical activities. For instance, Gerard et al reported that the amide derivatives of camphanic acid showed considerable antidiabetic activity (Figure b) .…”
Section: Introductionmentioning
confidence: 99%
“…26−28 Moreover, camphor has been used for the synthesis of many derivatives, which exhibited diverse pharmaceutical activities (Figure 1b). 29,30 Among them, some camphor derivatives were found to exhibit promising antifungal activities against different plant pathogenic fungi. 31,32 In addition, camphanic acid was a downstream product of camphor, and its derivatives also displayed promising pharmaceutical activities.…”
Section: ■ Introductionmentioning
confidence: 99%